HUBUNGAN EXSPLOSIVE POWER OTOT LENGAN DAN BAHU TERHADAP HASIL TOLAK PELURU GAYA O’BRIEN SISWA PUTRA KELAS X IPS1 SMAN 1 SUNGAI APIT - Yuskri Akbar; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations conducted by researchers in the field on male students of class X IPS1 SMAN 1 Sungai Apit who conducted physical education on bullet-proof material and were found during repulsion, resulting in students who were classified as low, or categorized as less or not according to standards. The minimum completeness criterion (KKM) given by the corner teacher to reject the bullet is 7.0 - 7.99 M with a standard score of 80, while there are still many class 1 students who have not reached the specified standard, this can still be maintained by the arm muscles and the shoulders of the male students of class X IPS1. The purpose of this study was to study the relationship of arm and shoulder muscle strength with O'Brien style bullet reject results for male students of class X IPS1 at SMAN 1 Sungai Apit. This research was conducted at SMAN 1 Sungai Apit, Siak Regency, Gajah Mada Road, Sungai Apit District, Siak Regency. The research time was carried out in January to July 2019. The population in this study was male students of IPS1 class X SMAN 1 Sungai Apit, sponsored by 16 people. The sample in this study was taken from (total sampling) or the sampling technique taken by IPS1 grade X students of SMAN 1 Sungai Apit who collected 16 people. Based on the results of the research carried out and carried out through the processing of statistical data so that it can produce data between shoulder muscle strength and the results of o'brient style bullet rejections on male students of class X IPS 1 at SMAN 1 Sungai Apit obtained rcount = 0.259 rtabel (α = 0 , 05) = 0.482, It turns out that rcount < rtabel means the hypothesis is rejected and does not involve a meaningful relationship between Exsplosive power of the arm and shoulder muscles with the results of the o'brien style protective resistance of male students of class X IPS1 SMAN 1 Sungai Apit.Key Words: Exsplosive Power of the O'brien Style Arm and Shoulder Bullet Muscles